A framework for the application of standards, recommendations, and research on large screen displays in the function of new control rooms design. Issue 1 (28th June 2021) - Grozdanovic, Miroljub; Bijelic, Bojan; Janjic, Aleksandar
Abstract: Existing display systems in most control rooms in Serbia are built on obsolete technology. To enable functional monitoring by the operators, these control rooms need to be redesigned using modern technology in a way that will optimize human interaction with the control system. This paper provides a review of published literature regarding large screen displays as well as guidance from pertinent industry standards. A significant part of this paper discusses an analysis of a new display system design in the control room. Topics analyzed include the optimal dimensions of display systems, coding of visual information, colors used on display systems, interaction between the operator and the display system, and description of the content presented on display systems. This research represents a guideline for the future design of new control rooms in Serbia's railway, mining, electric power systems, and soybean flakes production.